Mn(II) ion coordination polymer and its preparation method and application

By using the MN (II) ionic parts polymer [Mn (H2O) 2H (5-CMOIA)] n as semiconductor materials, solving the problem of high energy consumption of photovoltaic/electrochemical water decomposition systems Efficient optoelectronic catalysis and hydrogen generation.

CN118994629BActive Publication Date: 2025-01-24SHAANXI SCI TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411482897.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing photoelectric/electrochemical water decomposition systems consume too much energy during hydrogen production, and the intermittent and low energy conversion efficiency of photochemical technology limit their large-scale application.

Method used

Mn(II) ion coordination polymer [Mn(H2O)2H(5-CMOIA)]n is used as an efficient semiconductor material and prepared through a one-pot solvothermal reaction method to form a one-dimensional cyclic chain and a three-dimensional infinitely extending chain along the b-axis. Supramolecular layered structure, used in the field of photoelectrocatalysis.

Benefits of technology

It improves the catalytic activity and decentralization of optoelectronic catalysis, realizes high -efficiency optical energy conversion and hydrogen generation, and solves the problem of high energy consumption and low efficiency in traditional technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994629B_ABST
    Figure CN118994629B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of photoelectrocatalytic development, and in particular to a Mn(II) ion coordination polymer and a preparation method and application thereof. The present invention provides a Mn(II) ion coordination polymer and a preparation method and application thereof, and a Mn(II) ion coordination polymer is prepared, and the chemical expression of a single molecule thereof is [Mn(H2O)2H(5-CMOIA)] n , with manganese (II) as the central ion, two adjacent Mn (II) ions are connected by H (5-CMOIA) 2‑ The ligands are linked by bridged coordination to form a one-dimensional ring chain that extends infinitely along the b axis. In addition, adjacent one-dimensional chains are interconnected and continuously extended through intermolecular forces, eventually forming an infinite three-dimensional supramolecular layered structure. The Mn(II) ion coordination polymer has good dispersibility in solution and can be applied in the field of photoelectrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectrocatalysis, and in particular to a Mn(II) ion coordination polymer and a preparation method and application thereof. Background Art

[0002] In recent years, the demand for energy in industrial production and transportation equipment has increased, the combustion of fossil energy has caused serious energy losses, and the shortage of fossil fuel resources has become a major problem in the development of modern society. More and more researchers believe that hydrogen energy (H2) is the most representative green and sustainable energy. Obtaining clean hydrogen from water is a fascinating method that can be used to meet the growing energy demand and environmental challenges. In recent decades, a lot of effort has been spent on developing efficient and stable photoelectric / electrochemical (PEC) water splitting systems. In general, electrolyzers have the advantages of scalability, large output, and high stability under various conditions. However, the overpotential of the electrode is too large, which increases the energy consumed by the hydrogen production process. In contrast, photochemical technology is more energy-efficient and potentially cost-effective, but its intermittent and low energy conversion efficiency seriously hinder its large-scale application. Therefore, it is very necessary to develop solar-driven electrochemical technology that combines the advantages of both electrochemical and photochemical processes.

[0003] Coordination polymers (CPs) are crystalline solids with infinite structures, which are maintained by coordination bonds between metal ions or metal clusters and organic linker molecules, including metal organic frameworks (MOFs) as a subclass of CPs. In the field of catalysis, the application of MOFs in photoelectrocatalysis is a promising research direction, because MOFs can promote the transport of substrates / products and the exposure of active centers, shortening the transport distance of carriers. CPs can be divided into chain (1D) and framework (2D / 3D) structures in terms of topological structure. Compared with the CPs framework, the one-dimensional structure has the advantages of simple topological type in terms of coordination array, monomer diversity, and controllable synthesis method. In addition, their relatively high solubility makes it easy to analyze their chemical structure. Based on the above advantages, the present invention attempts to synthesize one-dimensional structured CPs with different metal ions using pyridazine derivatives as ligands, and determine their basic structure and properties by directional modification and characterization of the target molecules, and use an electrochemical workstation to study the photoelectrocatalytic performance of the target coordination polymer. At the same time, the application of one-dimensional structured CPs in the field of photoelectrocatalysis further expands the application of coordination polymers in the field of photoelectrocatalysis. Summary of the invention

[0004] The present invention provides a Mn(II) ion coordination polymer and a preparation method and application thereof. A Mn(II) ion coordination polymer is prepared, and the chemical expression of a single molecule thereof is [Mn(H 2 O) 2H(5-CMOIA)] n , with Mn(II) as the central ion, two adjacent Mn(II) ions are reacted by H(5-CMOIA) 2- The ligands are linked by bridges to form a one-dimensional ring chain that extends infinitely along the b axis. In addition, adjacent one-dimensional chains are interconnected and extended continuously through intermolecular forces, eventually forming an infinite three-dimensional supramolecular layered structure with good dispersibility in solution, which can be applied in the field of photoelectrocatalysis.

[0005] In order to solve the above technical problems, the present invention provides a Mn(II) ion coordination polymer, wherein the chemical expression of the Mn(II) ion coordination polymer is [Mn(H 2 O) 2 H(5-CMOIA)] n , where ligand H(5-CMOIA) 2- For the deprotonated H 3 (5-CMOIA), the H 3 (5-CMOIA) is 5-[3-carboxy-5-methyl-4-oxopyridazin-1(4H)-yl]isophthalic acid.

[0006] The present invention also provides a method for preparing the above-mentioned Mn(II) ion coordination polymer, comprising the following steps:

[0007] S1, manganese salt and H 3 (5-CMOIA) is added to acetonitrile to obtain a mixed solution, and after adjusting the pH value of the mixed solution, the mixed solution is kept at a high temperature for full reaction to obtain a reaction product;

[0008] S2, cooling the intermediate product prepared in S1 to crystallize, and washing, filtering and drying the precipitated crystals in sequence to obtain a Mn(II) ion coordination polymer.

[0009] According to the method for preparing a Mn(II) ion coordination polymer provided by the present invention, the manganese salt in S1 is any one of manganese nitrate, manganese carbonate and manganese chloride.

[0010] According to the preparation method of the Mn(II) ion coordination polymer provided by the present invention, the H 3 The structural formula of (5-CMOIA) is:

[0011] .

[0012] According to the preparation method of the Mn(II) ion coordination polymer provided by the present invention, the manganese salt, H 3The molar volume ratio of (5-CMOIA) to acetonitrile is 0.75 mmol:0.25 mmol:2 mL, the pH value of the mixed solution after adjustment is 2.9-3.1, the temperature of the isothermal full reaction is 90°C, and the time of the isothermal full reaction is 72 h.

[0013] According to the method for preparing a Mn(II) ion coordination polymer provided by the present invention, the solution for adjusting the pH of the mixed solution in S1 is a glacial acetic acid solution, and the concentration of the glacial acetic acid solution is 0.5 mol / L.

[0014] According to the preparation method of the Mn(II) ion coordination polymer provided by the present invention, the solvent used for the rinsing in S2 is deionized water, the filtration is reduced pressure filtration, and the drying condition is constant temperature drying in an oven at 30° C. for 5 h.

[0015] The present invention also provides an application of the above-mentioned Mn(II) ion coordination polymer, wherein the Mn(II) ion coordination polymer [Mn(H 2 O) 2 H(5-CMOIA)] n Used as a highly efficient semiconductor material in photoelectrocatalysis.

[0016] In the present invention, the Mn(II) ion coordination polymer has Mn(II) as the central ion, and two adjacent Mn(II) ions are connected by H(5-CMOIA) 2- The ligands are linked by bridges to form a one-dimensional ring chain that extends infinitely along the b axis. In addition, adjacent one-dimensional chains are connected to each other through intermolecular forces and continue to extend, eventually forming an infinite three-dimensional supramolecular layered structure.

[0017] The Mn(II) ion coordination polymer crystal of the present invention belongs to the triclinic system, P -1 Space group, unit cell parameters are a=6.8408(7), b=8.5417(7), c=12.9045(13), α=100.179(4), β=98.788(4), γ=91.267(4), V=732.52(12) Å 3 .

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The present invention adopts a one-pot solvent thermal reaction method to prepare Mn(II) ion coordination polymer [Mn(H 2 O) 2 H(5-CMOIA)] n The preparation method has the advantages of simple process, convenient operation, high yield and good reproducibility.

[0020] 2. The Mn(II) ion coordination polymer prepared in the present invention has good dispersibility in the solution and strong catalytic activity, and can be applied in the field of photoelectrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a single molecule image of the Mn(II) ion coordination polymer prepared in Example 2;

[0022] Figure 2 is the one-dimensional ring chain structure of the Mn(II) ion coordination polymer prepared in Example 2;

[0023] Figure 3 is the three-dimensional supramolecular structure of the Mn(II) ion coordination polymer prepared in Example 2;

[0024] Figure 4 is the IR graph of the Mn(II) ion coordination polymer measured in Example 5;

[0025] Figure 5 is the XRD pattern of the Mn(II) ion coordination polymer measured in Example 5;

[0026] Figure 6 is a cyclic voltammetry curve of the Mn(II) ion coordination polymer measured in Example 5 in the dark and under xenon lamp irradiation;

[0027] Figure 7 is a polarization curve diagram of the Mn(II) ion coordination polymer under LSV measured in Example 5;

[0028] Figure 8 This is a photocurrent response curve of the Mn(II) ion coordination polymer measured in Example 5 under LSV. DETAILED DESCRIPTION

[0029] Example 1

[0030] This embodiment provides a H 3 The specific steps of the preparation method of (5-CMOIA) are as follows.

[0031] S1. Add 25 g of 5-aminoisophthalic acid and 200 mL of anhydrous ethanol to a 250 mL single-necked bottle, stir to obtain reaction solution 1, then add 25 mL of thionyl chloride dropwise. With the addition of thionyl chloride, the reaction solution 1 gradually becomes clear. After a period of time, it becomes a white turbid solution. After all the drops are added, reflux and stir at 80 °C for 5 h. After cooling to room temperature, a large amount of white solid precipitates. Concentrate to obtain a white solid crude product.

[0032] Ethyl acetate was added to dissolve the crude white solid product, the pH of the solution was adjusted to neutral, and the solution was transferred to a separatory funnel and allowed to stand for separation; the aqueous phase was extracted three times and the organic phases were combined, and the combined organic phases were extracted with water, the aqueous phase flowed out from the bottom, and the organic phase was poured out from the mouth. The separated organic phase was dehydrated and filtered, and concentrated to obtain white solid diethyl 5-aminoisophthalate;

[0033] S2. Add 6 g of 5-aminoisophthalic acid diethyl ester and 100 mL of distilled water to a 500 mL single-necked bottle, stir evenly, and add 30 mL of 40% concentrated hydrochloric acid dropwise under ice bath conditions to obtain a mixed solution. Take 2.7 g of NaNO 2 Dissolve in 50 mL of distilled water to obtain NaNO 2 solution, and then add NaNO dropwise to the mixed solution again. 2 Solution, to obtain a yellow clear reaction solution 2;

[0034] S3, add 13.5 g of sodium acetate and 100 mL of distilled water to a 1000 mL flask to dissolve, then add 175 mL of anhydrous ethanol, stir at 0 °C for 25 min, add 10 g of ethyl propionyl acetate, continue stirring for 20 min, then add reaction solution 2 dropwise, the solution gradually turns yellow, and a bright yellow solid precipitates as the diazonium salt is added. The reaction ends after 3 h to obtain a yellow turbid reaction solution 3, filter to obtain a filter cake, wash the filter cake to neutrality to obtain a bright yellow filter cake, and dry at room temperature to obtain a bright yellow solid diethyl (E)-5-[2-(1-ethoxy-1,3-dioxaalkane-2-ylidene) hydrazide] isophthalate;

[0035] S4. Add 10.5 g of diethyl (E)-5-[2-(1-ethoxy-1,3-dioxaalkane-2-ylidene)hydrazide]isophthalate and 100 mL of toluene to a 500 mL single-necked bottle, dissolve by ultrasonication to obtain a yellow clear reaction solution 4, add 4.3 g of DMF-DMA ( N,N -dimethylformamide dimethyl acetal), the solution color turned black purple, and refluxed at 90 °C while being monitored by TLC. The reaction was completed after 12 h;

[0036] Join CH 2 Cl 2 After being fully dissolved, a white solid was precipitated by ultrasonication, and then refluxed and stirred for 10 h, and then allowed to stand and filtered to obtain a filter cake, which was washed with petroleum ether to obtain a white-yellow solid 5-[3-(ethoxycarbonyl)-5-methyl-4-oxopyrazine-1(4H)-yl]isophthalate;

[0037] S5. Add 9.5 g of 5-[3-(ethoxycarbonyl)-5-methyl-4-oxopyrazine-1(4H)-yl]isophthalic acid ester and 150 mL of distilled water to a 500 mL single-necked bottle, stir evenly, then add 6.2 g of sodium hydroxide, heat to 60 °C, reflux to obtain a reddish brown solution reaction solution 5. After 3 h of reaction, the solution turns purple-red. After cooling to room temperature, add 150 mL of distilled water to the reaction bottle, adjust the pH to 2, and precipitate flesh-colored solid 5-[3-carboxyl-5-methyl-4-oxopyridazine-1(4H)-yl]isophthalic acid. Filter to obtain a filter cake, wash the filter cake until neutral and dry to obtain a flesh-colored powder, which is H 3 (5-CMOIA).

[0038] The prepared H 3 The structural formula of (5-CMOIA) is:

[0039] .

[0040] Example 2

[0041] This embodiment provides a method for preparing a Mn(II) ion coordination polymer, and the specific method is as follows.

[0042] S1, 0.75 mmol of manganese chloride tetrahydrate, 0.25 mmol of H 3 (5-CMOIA) was added to a glass scintillation vial containing 2 mL of acetonitrile solvent and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 3.1 with a 0.5 mol / L glacial acetic acid solution. The mixed solution was subjected to solvothermal isothermal reaction at 90 °C for 72 h to obtain a reaction product.

[0043] S2. The reaction product obtained in S1 is cooled and crystallized to obtain a crystallized product. The crystallized product is washed with deionized water, and then filtered under reduced pressure to obtain a transparent block crystal. The transparent block crystal is placed in an oven at a temperature of 60° C. for 5 h to obtain a Mn(II) ion coordination polymer. The molecular formula of the Mn(II) ion coordination polymer is [Mn(H 2 O) 2 H(5-CMOIA)] n , the yield is about 71.6%.

[0044] The Mn(II) ion coordination polymer prepared in this example has Mn(II) as the central ion, and two adjacent Mn(II) ions are connected by H(5-CMOIA) 2- The ligands are linked by bridges to form a one-dimensional ring chain that extends infinitely along the b axis, such as Figure 2In addition, adjacent one-dimensional chains are connected to each other through intermolecular forces and continue to extend, eventually forming an infinite three-dimensional supramolecular layered structure.

[0045] Example 3

[0046] This embodiment provides a method for preparing a Mn(II) ion coordination polymer, and the specific method is as follows.

[0047] S1. Mix 0.75 mmol of manganese nitrate tetrahydrate and 0.25 mmol of H 3 (5-CMOIA) was added to a glass scintillation vial containing 2 mL of acetonitrile solvent and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 2.9 with a 0.5 mol / L glacial acetic acid solution. The mixed solution was subjected to solvothermal isothermal reaction at 90 °C for 72 h to obtain a reaction product.

[0048] S2. The reaction product obtained in S1 is cooled and crystallized to obtain a crystallized product, the crystallized product is rinsed with deionized water, and then filtered under reduced pressure to obtain transparent block crystals, and the transparent block crystals are placed in an oven at a temperature of 60° C. for 5 h to obtain a Mn(II) ion coordination polymer with a yield of about 70.4%.

[0049] Example 4

[0050] This embodiment provides a method for preparing a Mn(II) ion coordination polymer, and the specific method is as follows.

[0051] S1, 0.75 mmol of manganese carbonate, 0.25 mmol of H 3 (5-CMOIA) was added to a glass scintillation vial containing 2 mL of acetonitrile solvent and mixed evenly to obtain a mixed solution. The pH value of the mixed solution was adjusted to 3.0 with a 0.5 mol / L glacial acetic acid solution. The mixed solution was subjected to solvothermal isothermal reaction at 90 °C for 72 h to obtain a reaction product.

[0052] S2. The reaction product obtained in S1 is cooled and crystallized to obtain a crystallized product, the crystallized product is rinsed with deionized water, and then filtered under reduced pressure to obtain transparent block crystals, and the transparent block crystals are placed in an oven at a temperature of 60° C. for 5 h to obtain a Mn(II) ion coordination polymer with a yield of about 69.5%.

[0053] Example 5

[0054] The Mn(II) ion coordination polymer prepared in Example 2 was characterized.

[0055] (1) Crystal structure determination of Mn(II) ion coordination polymer

[0056] A single crystal with a size of 0.180×0.210×0.220 mm was selected under a microscope and X-ray diffraction experiments were carried out at room temperature.

[0057] Diffraction data were collected on a Bruker-ApexП X-ray single crystal diffractometer. Mo-Kα rays (λ = 0.71073 Å) were monochromatized with a graphite monochromator, and diffraction points were collected in ω-2θ scanning mode. All data were corrected by factors and empirical absorption. The crystal structure was solved by a direct method using a program. Hydrogen atoms were determined by difference Fourier synthesis and fixed at the calculated optimal positions. All non-hydrogen atoms and their anisotropic thermal parameters were corrected based on the full matrix least squares method using the SHELX-97 program. The main crystallographic measurement data of the Mn(II) ion coordination polymer are shown in Table 1. The important bond length and bond angle data of the Mn(II) ion coordination polymer are shown in Table 2. The crystal structure is shown in Figure 1 As shown, the three-dimensional supramolecular structure of the polymer is observed from the b-axis direction, as Figure 3 shown.

[0058] Table 1

[0059]

[0060] Table 2

[0061]

[0062] In Table 1, a, b and c represent the edge lengths of the crystal in the directions of the three crystal axes, respectively, and α, β and γ represent the angles between a and b, a and c, and b and c, respectively; Z is the number of molecules contained in the unit cell; the diffraction index range of the limiting factor is (h, k, l); F (000) is the number of electrons in the unit cell; Final R indices I >2σ( I )] is the residual factor R value for the observable diffraction point; R is the non-weighted consistency factor; R 1 and wR 2 All are weight consistency factors;

[0063] In the first row of Table 2, Mn1 refers to Mn atom 1 in the Mn (II) ion coordination polymer single crystal, O2#1 refers to the symmetric atom 1 of O atom 2 in the Mn (II) ion coordination polymer single crystal, and Mn1- O2#1 represents the bond length between the symmetric atoms of Mn atom 1 and O atom 2, and the bond length is 2.2318±13, with 13 being the standard deviation;

[0064] O2#1- Mn1-O2#2 represents the bond angle between the symmetric atom 1 of O atom 2, the symmetric atom 2 of Mn atom 1 and the symmetric atom 2 of O atom 2, and the bond angle is 77.61±5;

[0065] The same applies to other data in the table.

[0066] (2) Infrared (IR) spectrum characterization

[0067] Figure 3 The coordination polymer of Mn(II) ion and H 3 IR spectrum of (5-CMOIA), the sample infrared spectrum data collection is 4000~500cm -1 , using KBr pellets, Figure 4 It can be seen that at about 3600-3200 cm -1 The stretching vibration peak of -OH was observed at 1420-1300 cm -1 The strong peak at corresponds to H 3 (5-CMOIA) carboxylate group (-COO - ) vibration.

[0068] (3) Phase purity characterization of Mn(II) ion coordination polymers

[0069] The powder XRD characterization results of the Mn(II) ion coordination polymer using a Bruker / D8Advance X-ray diffractometer showed that it had reliable phase purity, such as Figure 5 shown.

[0070] (4) Photoelectrocatalytic performance of Mn(II) ion coordination polymers

[0071] In order to evaluate the photoelectrochemical ability of Mn(II) ion coordination polymer, the Mn(II) ion coordination polymer powder was coated on an area of ​​1.0 cm in a three-electrode environment consisting of ITO conductive glass, carbon rod, and saturated calomel electrode. 2 The surface of ITO conductive glass was treated with 0.5 mol / L Na 2 SO 4 As the electrolyte, the Mn(II) ion coordination polymer was subjected to cyclic voltammetry (CV) before and after irradiation with a photocatalytic xenon lamp at a scan rate of 50 mV / s. Figure 6 shown.

[0072] According to the cyclic voltammetry curves of the Mn(II) ion coordination polymer in the dark and light environment, the polarization curve of the Mn(II) ion coordination polymer was scanned by linear voltammetry (LSV) at a scan rate of 5 mV / s to obtain the overpotential required for the OER reaction before and after xenon lamp irradiation, such as Figure 7As shown. When measuring 1.25 mA / cm -2 The photocurrent response of the Mn(II) ion coordination polymer was tested at a current density of 1.5 volts to investigate its light response stability. The tests were performed alternately in dark and light environments at intervals of 50 s. The results are shown in Figure 2. Figure 8 shown.

[0073] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A Mn(II) ion coordination polymer, characterized in that: The chemical expression of the Mn(II) ion coordination polymer is [Mn(H2O)2H(5-CMOIA)] n , where ligand H(5-CMOIA) 2- is deprotonated H3(5-CMOIA), wherein H3(5-CMOIA) is 5-[3-carboxyl-5-methyl-4-oxopyridazine-1(4H)-yl]isophthalic acid, with Mn(II) as the central ion, and two adjacent Mn(II) ions are separated by H(5-CMOIA) 2- The bridging coordination link of the ligand.

2. A method for preparing the Mn(II) ion coordination polymer as claimed in claim 1, characterized in that: The following steps are involved: S1, adding manganese salt and H3(5-CMOIA) to acetonitrile to obtain a mixed solution, adjusting the pH value of the mixed solution, and then fully reacting the mixed solution at a constant temperature of 90° C. to obtain a reaction product, wherein the pH value of the mixed solution is 2.9 to 3.1; S2, cooling the intermediate product prepared in S1 to crystallize, and washing, filtering and drying the precipitated crystals in sequence to obtain a Mn(II) ion coordination polymer.

3. The method for preparing the Mn(II) ion coordination polymer according to claim 2, characterized in that: The manganese salt in S1 is any one of manganese nitrate, manganese carbonate and manganese chloride.

4. The method for preparing the Mn(II) ion coordination polymer according to claim 2, characterized in that: The molar volume ratio of the manganese salt, H3(5-CMOIA) and acetonitrile in S1 is 0.75 mmol:0.25 mmol:2 mL, and the isothermal reaction time is 72 h.

5. The method for preparing the Mn(II) ion coordination polymer according to claim 2, characterized in that: The solution for adjusting the pH of the mixed solution in S1 is a glacial acetic acid solution, and the concentration of the glacial acetic acid solution is 0.5 mol / L.

6. The method for preparing the Mn(II) ion coordination polymer according to claim 2, characterized in that: The solvent used for the washing in S2 is deionized water, the filtration is reduced pressure filtration, and the drying condition is constant temperature drying in an oven at 30° C. for 5 h.

7. An application of the Mn(II) ion coordination polymer as claimed in claim 1, characterized in that: The Mn(II) ion coordination polymer is used as a highly efficient semiconductor material in photoelectrocatalysis.

Citation Information

Patent Citations

  • Divalent manganese ion coordination polymer as well as preparation method and application thereof

    CN118374007A

  • Pyridazine hydrogen bond skeleton fluorescence sensing material and preparation method and application thereof

    CN118546389A